Microglial Drug Targets in AD: Opportunities and Challenges in Drug Discovery and Development - Biber, Knut; Bhattacharya, Anindya; Campbell, Brian M.; Piro, Justin R.; Rohe, Michael; Staal, Roland G.W.; Talanian, Robert V.; Möller, Thomas (Frontiers in Pharmacology, 2019)
Alzheimer’s disease (AD) is an increasing burden to society and healthcare systems, and one of the biggest unmet medical needs with no disease-modifying treatment. Genetic evidence from genome wide association (GWAS) studies and gene network analysis have clearly revealed a key role of the innate immune system in the brain, of which microglia are the most important element. ‘Single nucleotide polymorphisms (SNPs) in genes predominantly expressed in microglia have been associated with altered risk of developing AD. Furthermore, microglia-specific pathways are affected on the mRNA expression level in post-mortem AD tissue and in mouse models of AD. Together these findings have increased the interest in microglia biology, and numerous scientific reports have proposed microglial molecules and pathways as drug targets for AD. Target identification and validation are generally the first steps in drug discovery. Both target validation and drug lead identification for central nervous system (CNS) targets and diseases entail additional significant obstacles compared to peripherally restricted targets and diseases. This makes CNS drug discovery, even with well-validated targets, challenging. In this article, we will illustrate the special challenges of AD drug discovery by discussing the viability/practicality of possible microglia drug targets including CD33, Kca3.1, Kynurenines, P2X7, PD1, TLRs, and TREM2.